Supports and gaps in federal policy for addressing racial and ethnic disparities among long-term care facility residents. Issue 4 (18th May 2020) - Mauldin, Rebecca L.; Lee, Kathy; Tang, Weizhou; Herrera, Sarah; Williams, Antwan
ABSTRACT: Older adults from racial and ethnic minority groups are likely to face disparities in their health as well as care experiences in long-term care facilities such as nursing homes and assisted living facilities just as they do in the United States as a whole. Policymakers in the United States face concerns around long-term services and supports to address the growing demands of a rapidly aging population through public and private sector initiatives. It is important to create inclusive and culturally responsive environments to meet the needs of diverse groups of older adults. In spite of federal policy that supports minority health and protects the well-being of long-term care facility residents, racial and ethnic disparities persist in long-term care facilities. This manuscript describes supports and gaps in the current United States' federal policy to reduce racial and ethnic disparities in long-term care facilities. Implications for social workers are discussed and recommendations include efforts to revise portions of the Patient Protection and Affordable Care Act of 2010, amending regulations regarding long-term care facilities' training and oversight, and tailoring the Long-Term Care Ombudsman Program's data collection, analysis, and reporting requirements to include racial and ethnic demographic data.